Complex study of Neogenous Deposit thickness of pannon basin on the basis of seismostratigraphic approaches with elements of Seismofacial analysis - Olneva Tatiana V.; Zhukovskaya Elena A. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Санкт-Петербургский горный университет», 2017)
From 2011 to 2017, large-scale seismic surveys were carried out by PJSC Gazprom Neft within the Pannonian Basin (territory of Serbia). Currently, the coverage area of seismic surveys in the modification of MOGT 3D is approaching the stage of regional study and is about 5,600 km2. The obtained data signify a new stage in the geological study of the region and represent a rich material for further understanding of the geological structure of the research area. The full-scale introduction of seismic prospecting in the modification of the MOGT 3D has made it possible to use modern approaches to interpretation, such as seismostratigraphic and seismic facies analysis. On the one hand, the results obtained contribute to a more successful geological exploration. On the other hand, the adaptation of seismostratigraphic approaches, sequestration techniques and seismic facies analysis techniques to the regional features of the Pannonian basin makes it possible to develop the methods themselves, since the subject of research, in the opinion of many scientists, is in many senses a natural laboratory. The article describes the main seismostratigraphic complexes, the principles of their isolation, the features of interpretation approaches for seismic facies analysis in each of them, and the results of seismic facies analysis are combined with core studies. Within this region, more than 500 deposits with total reserves of over 1,400 million tons of conventional oil have been discovered. Despite the small size of the vast majority of deposits, they are profitable and further exploration is of great practical interest.
Keywords: Pannonian basin; Neogene; seismostratigraphy; seismostratigraphic complex; interpretation of seismic data; seismic facies analysis; sedimentation model; Cenozoic::Neogene; Кайнозой::Неоген